2009
DOI: 10.1016/j.healun.2009.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Immunoglobulin Decreases the Risk of Cytomegalovirus Infection but not Disease After Pediatric Lung Transplantation

Abstract: A retrospective review of pediatric lung transplant recipients at fourteen sites in North America and Europe was conducted to evaluate the impact of adding cytomegalovirus immunoglobulin (CMVIG) prophylaxis to at least three weeks of intravenous ganciclovir in pediatric lung transplant recipients. Data were recorded for the first year after transplantation. Associations between time to CMV and risk factors, including CMVIG use, were assessed by multivariable Cox proportional hazards models. Of 599 subjects who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 27 publications
0
19
0
1
Order By: Relevance
“…Krampe et al found a low incidence of CMV disease in 28 pediatric liver transplant recipients receiving IVIG and preemptive therapy but did not have a comparison group (241). In a retrospective review of 329 pediatric lung transplant recipients, of whom 62 (19%) received CMV Ig in addition to at least 3 weeks of intravenous ganciclovir, CMV Ig was associated with a decreased risk of CMV infection but did not impact the incidence of CMV disease, acute rejection, or early morbidity (243). In one prospective randomized pediatric study that primarily targeted Epstein-Barr virus, CMV Ig did not appear to have a significant impact on the development of CMV disease, although there was a trend toward a higher 2-year CMV disease-free rate in R+ children (216).…”
Section: Prevention Of Pediatric CMV Diseasementioning
confidence: 99%
“…Krampe et al found a low incidence of CMV disease in 28 pediatric liver transplant recipients receiving IVIG and preemptive therapy but did not have a comparison group (241). In a retrospective review of 329 pediatric lung transplant recipients, of whom 62 (19%) received CMV Ig in addition to at least 3 weeks of intravenous ganciclovir, CMV Ig was associated with a decreased risk of CMV infection but did not impact the incidence of CMV disease, acute rejection, or early morbidity (243). In one prospective randomized pediatric study that primarily targeted Epstein-Barr virus, CMV Ig did not appear to have a significant impact on the development of CMV disease, although there was a trend toward a higher 2-year CMV disease-free rate in R+ children (216).…”
Section: Prevention Of Pediatric CMV Diseasementioning
confidence: 99%
“…However, this protective effect of mAbs was observed in seronegative patients, whereas our study is focused on seropositive recipients. While observational studies reported conflicting results, 2 randomized studies reported protection against both infection and disease . In addition, a meta‐analysis study conducted a few years ago, which analyzed 11 randomized SOTR trials (about 700 patients), reported that HCMV IG administration was associated with improved survival, reduced HCMV disease and HCMV‐associated death …”
Section: Discussionmentioning
confidence: 99%
“…The protective effect of antibodies was suggested by experimental findings in the mouse CMV model, where lethal infection in immune‐deficient mice was prevented . Similarly, in SOTR, several observational studies have claimed the protective effect of IG against HCMV infection, in addition to a partial protection from HCMV disease and improved survival both in adult and pediatric patients receiving thoracic, kidney, or liver transplant . Randomized trials provided discordant results on the efficacy of IG in seronegative recipients of kidney or liver from seropositive donors (thus, at risk for primary infection), whereas a recent randomized trial showed the efficacy of mAbs in preventing HCMV disease in seronegative kidney recipients …”
Section: Introductionmentioning
confidence: 99%
“…İmmünglobulin tedavisi (IVIG (intravenöz immünglobulin) ve CMVIG (CMV immünglobulin)) hem önlem stratejileri içinde hem de CMV hastalığında yeri tartışmalı bir uygulamadır. NAPRTCS çalışmasında CMVIG profilaksisinin IVIG+antiviral tedaviye göre CMV hastalığına bağlı hastaneye yatış sıklığını azalttığı gösterilse de sonraki çalışmalarda bu yöntemin CMV enfeksiyonunu azalttığı ancak CMV hastalığını azaltmadığı gösterilmiştir (60).…”
Section: Hibrit Yaklaşımunclassified